‘You Are Thai, Why Don’t You Do It?’ An anthropological study of Thai women’s strategies for navigating sexualized and racialized stigma in the Thai massage industry in Sweden - Hammargren,Nicola (2025)
This study explores how Thai women in Sweden, working in the massage and wellness sector and members of the ThaiWISE initiative, navigate social stigma and negotiates their identities in the context of migration. Drawing on five semi-structured interviews, the study examines how these women manage the persistent association between Thai femininity and sex work, despite working in safe and regulated environments. Through a qualitative, ethnographic approach informed by social anthropology, the analysis highlights the strategies these women use to reclaim respectability and legitimacy, such as through community support, professional certification and impression management. The study engages with theoretical concepts including Goffman’s stigma and impression management, Pheterson’s whore stigma, and Rytter’s integration paradigm. Findings suggest that while integration into safe workspaces enables opportunities and self-sufficiency, Thai women must continuously manage both external prejudice and internalized stigma. Additionally, community-based initiatives like ThaiWISE play a crucial role in fostering resilience, professional legitimacy and collective solidarity. The thesis aims to contribute to discussions on migration, gendered labor and the everyday negotiation of stigma.
Keywords: Social anthropology; Thai women; stigma; gendered labor; massage